Use of palliative chemotherapy in patients aged 80 years and over with incurable cancer: experience at three Sydney cancer centres. Issue 1 (January 2017) - Ip, E.; Pokorny, A. M. J.; Della‐Fiorentina, S.; Beale, P.; Bray, V.; Kiely, B. E.; Blinman, P.
Abstract : Background: Octogenarians represent a growing population reviewed in medical oncology clinics, yet there is a paucity of data on how chemotherapy is tolerated in this age group. Aim: To describe the use of palliative first‐line chemotherapy in patients 80 years and over and factors associated with its use. Methods: We identified all new patients aged 80 years or older diagnosed with incurable advanced solid organ cancer and seen in one of three Sydney medical oncology outpatient clinics between January 2009 and December 2013. Patient, disease and treatment details were summarised and factors associated with chemotherapy use explored. Results: Of 420 eligible patients, 100 (24%) started first‐line chemotherapy. Younger age at diagnosis was the only factor associated with receiving chemotherapy (median 82.9 vs 84.1 years, P  = 0.002). A total of 78% of patients had single‐agent chemotherapy, and 41% received a full dose for the first cycle. During treatment, 54% experienced toxicity, necessitating dose reduction, delay or omission, and 32% were hospitalised. These events were associated with receipt of combination chemotherapy (OR 5.1; P  = 0.04) and full‐dose chemotherapy for cycle 1 (OR 3.5; P  = 0.02). Radiological disease control was achieved in 60%. Chemotherapy was stopped because of progressive disease (48%), toxicity (37%) or completion of planned course (17%). Conclusion: A quarter of patients 80 years and older received first‐line palliative chemotherapy. Despite most receiving a modified dose, one third were hospitalised during treatment. These findings highlight the need for careful clinical assessment and selection of older cancer patients for chemotherapy.